KEBIJAKAN PENGEMBANGAN WISATA KOTA DALAM MENCIPTAKAN PENDAPATAN ASLI DAERAH KABUPATEN BUNGO - Dedi Epriadi; Mardansyah Mardansyah; Joko Setyoko (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Implementation of development in various aspects of life which was organized by the government at various levels, is actually a part of the desire to create a common goal of realizing a just, prosperous, and prosperous. Development of tourism sector in this country become increasingly attractive, because it is closely related to the economic life of society. That is, development in this field, will trigger the birth of the centers of new growth that is driven directly by the public, either in small, medium, or large. Tourism development as another name for the development of tourism sector, has now experienced a shift of meaning that we must continue to follow its development. First person to speak just travel in order to find a calm and peaceful and away from the hustle and bustle of life that are a routine. Variety of potential new tourism continues to be opened and developed by all local governments in Indonesia. Diverse facilities and infrastructure continues to equipped and equally important, access to transportation to the attraction opened in such a way, in the hope of the people in droves to visit. Keywords : Policy, City Tourism, Local Original Income